Judicial Review on Administrative Action: Reflection on the Bank Century Bailout Policy - Sitorus, Lily Evelina (Indonesia Law Review, 2016)
Accountability is the key to good governance. In global administrative law, every policy made should be accountable. The given law should be accessible to the public. At the time of the global financial crisis, many countries did not have the necessary rules to solve the problems that arose. In Indonesia, the government’s decision to bail out Bank Century has remained controversial up to the present time. The need for a comprehensive law dealing with economic, political and social factors should be considered. The Indonesian Law regarding Government Administration provides for the code of conduct for government action. An entire chapter in the law has been dedicated to set out provisions on discretion, reflecting a two-way approach, namely: restriction of government action on the one hand and the protection of public rights on the other. In practice, however, such rule is not implemented in line with the intended formulation. There is still a need for harmonization with the law regarding State Administration Courts in Indonesia.